Immunothrombosis and Complement Activation Contribute to Disease Severity and Adverse Outcome in COVID-19 - Tiphaine Ruggeri; Yasmin De Wit; Noëlia Schärz; Gerard van Mierlo; Anne Angelillo-Scherrer; Justine Brodard; Joerg C. Schefold; Cédric Hirzel; Ilse Jongerius; Sacha Zeerleder (Karger Publishers, 2023)
Severe COVID-19 is characterized by systemic inflammation and multiple organ dysfunction syndrome (MODS). Arterial and venous thrombosis are involved in the pathogenesis of MODS and fatality in COVID-19. There is evidence that complement and neutrophil activation in the form of neutrophil extracellular traps are main drivers for development of microvascular complications in COVID-19. Plasma and serum samples were collected from 83 patients infected by SARS-CoV-2 during the two first waves of COVID-19, before the availability of SARS-CoV-2 vaccination. Samples were collected at enrollment, day 11, and day 28; and patients had differing severity of disease. In this comprehensive study, we measured cell-free DNA, neutrophil activation, deoxyribonuclease I activity, complement activation, and D-dimers in longitudinal samples of COVID-19 patients. We show that all the above markers, except deoxyribonuclease I activity, increased with disease severity. Moreover, we provide evidence that in severe disease there is continued neutrophil and complement activation, as well as D-dimer formation and nucleosome release, whereas in mild and moderate disease all these markers decrease over time. These findings suggest that neutrophil and complement activation are important drivers of microvascular complications and that they reflect immunothrombosis in these patients. Neutrophil activation, complement activation, cell-free DNA, and D-dimer levels have the potential to serve as reliable biomarkers for disease severity and fatality in COVID-19. They might also serve as suitable markers with which to monitor the efficacy of therapeutic interventions in COVID-19.